Social and economic development of monotowns in Kazakhstan - Omarova, A.T.; Shokhan, R.; Khoich, A.; Grelo, M.F.; Srailova, G.N. (BUKETOV BUSINESS REVIEW, 2019)
The article is devoted to the state of monotowns in the Republic of Kazakhstan. The condition of settlements in the administrative-territorial areas included in the category of monotowns has been studied. The main characteristics of the mono-industry classification, i.e. monotowns with the developed manufacturing enterprises, monotowns with the developted proccessing industry and scientific and industrial monotowns are grouped into monotowns. The current situation in the monotowns and the current state of the regions are analyzed. In the monotowns, engineering and utilities sectors, including heat, water, electricity network and housing degradation rates have been studied. The main objectives and tasks of the State Program for Regional Development till 2020 are considered. Within the framework of the objectives of defining investment priorities for each macro region, improvement of the territorial development of the country and the development of engineering infrastructure, housing and communal services, the achievable indicators of development of engineering networks in monotowns for 2019 are estimated. The problems of monotowns, concentrated in the largest industrial centers of the republic, have been identified and the solutions are presented. The experience of the countries such as USA, Sweden, Germany, etc. is considered in addressing monotowns. The focus on the state policy on regulation of the problems of domestic monotowns is highlighted.